Choosing parameters of the hydraulic drive with the variable pump on the basis of its stability investigation - Buriennikov, Yu. A.; Kozlov, L. H.; Repinskyi, S. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
In this paper basic circuit of the automatic regulator for the variable pump is proposed. The circuit incorporates combined control means that provide pump flow rate stabilization as well as constant-power operation of the pump. Mathematical model of the proposed circuit is presented. It is of determined how the control system parameters influence the dynamic characteristics and the stability of variables describing the control system conditions. The combination of the a regulator design parameters has been found that provides hydraulic drive stable operation both during the flow regulator operation. The necessary indicators of the transient processes quality are also defined.